TELAAH LITERATUR: EFEKTIVITAS PENERAPAN MEDIA GAME BERBASIS POWER POINT INTERAKTIF DALAM PEMBELAJARAN MATEMATIKA SISWA SEKOLAH DASAR - Nadia Tri Utami; Dewi Ilma Antawati (Archetype : Jurnal Ilmiah Psikologi dan Terapan, 2025)
Education plays a central role in shaping the character, understanding, and skills of individuals in the era of Society 5.0, which demands the integration of technology in education. However, the lack of teachers' knowledge of digital technology poses a significant challenge, especially in facing the changes in post-COVID-19 learning. The focus of this research is on student learning motivation, particularly in abstract subjects such as mathematics. This study proposes the development of interactive PowerPoint-based games as a solution to enhance the motivation for learning mathematics among elementary school students. Through a systematic review of relevant journal articles on Google Scholar, the author discusses the effectiveness of this instructional media in elementary school mathematics education. The review of 10 journals indicates that this instructional media is effective in improving the motivation for learning mathematics among elementary school students and can enhance students' critical thinking skills. This research demonstrates that the integration of interactive PowerPoint-based game instructional media has a positive impact on students' motivation levels, mathematics learning outcomes, participation, creativity, activities, as well as character formation, including independence, self-confidence, and tolerance. It contributes significantly to the achievement of mathematics learning outcomes. Keywords: education; student motivation; interactive games; math learning